MRI-Based Diagnosis of Neurocysticercosis with Coexisting Cervical and Lumbar Disc Pathology: A Case Report - Yadav, Sandeep; Vrinda; Kumar, Pankaj; Yadav, Santosh; Kumar, Dheeraj (Acta medica Lituanica, 2025)
Neurocysticercosis (NCC), a parasitic infection of the central nervous system caused by Taenia solium larvae, is a leading cause of acquired epilepsy in endemic regions. This case describes a 40-year-old male who presented with chronic headache, dizziness, and a recent seizure episode. He had no prior history of systemic illness, tuberculosis, or neurological disorders. Magnetic Resonance Imaging (MRI) of the brain revealed multiple ring-enhancing lesions with an eccentric scolex in the cerebral and cerebellar hemispheres, accompanied by surrounding edema, confirming the diagnosis of neurocysticercosis. Additional lesions in extraocular, facial, and tongue muscles were consistent with myocysticercosis, an uncommon but clinically significant manifestation that may mimic inflammatory or neoplastic processes.Spinal imaging demonstrated degenerative changes, including diffuse cervical disc bulges at multiple levels (C3–C7) and lumbar disc pathology at L4–L5, causing anterior thecal sac indentation but without cord compression or myelomalacia. While the spinal findings were incidental, they were clinically relevant as contributors to chronic pain and potential neurological deficits.The coexistence of disseminated neurocysticercosis with muscular involvement and early degenerative spinal disease highlights the importance of comprehensive evaluation in patients presenting with seizures and persistent headache. Treatment included albendazole-based antiparasitic therapy, corticosteroids to reduce perilesional edema, antiepileptic medications, and conservative management for disc disease.This case underscores the role of MRI in identifying pathognomonic features of cysticercosis, emphasizes the need for systemic evaluation, and demonstrates the significance of recognizing coexisting pathologies for tailored multidisciplinary management.